MINI PERCUTANEOUS NEPHROLITHOTOMY THROUGH UPPER CALYCEAL PUNCTURE IN PAEDIATRIC AGE PATIENTS: A SINGLE CENTRE STUDY - Rahman, Faiz Ur; Ahmad, Tariq; Izhar, Muhammad; Naeem, Muhammad; Khan, Riaz Ahmad; Khan, Irfanullah (Journal of Postgraduate Medical Institute, 2021)
Objective: To determine the outcome of Mini Percutaneous Nephrolithotomy (mPCNL) through upper calyceal puncture in pediatric age patients. Methodology: This cross-sectional study was conducted at the Department of Urology, Institute of Kidney Diseases, Peshawar from February 2018 to July 2019. A total of 30 children were enrolled using consecutive sampling. They underwent mini-PCNL through upper calyceal puncture for renal stone extraction. The patients were evaluated for different outcome variables. Data was entered in SPSS version 20 and descriptive statistics were calculated for all variables. Results: Out of 30 patients, mean age of the patients was 11.72 ± 2 years with range of 8-16 years. The stones had a mean size of 13.8 ± 3 mm. Maximum had single puncture (70%), while remaining (30%) had double puncture entrance. A high stone free rate was achieved (86.6% cases). The mean time for operation was 53 ± 15 minutes. In total, 2 children developed fever and 3 dropped hemoglobin of about 0.8 g/dl. Conclusion: mPCNL through upper calyceal puncture is an effective procedure for the management renal calculi in pediatric population. It has high stone free rate, less serious complications and short post-operative hospital stay.